Microstructure and mechanical properties of dissimilar NiTi and 304 stainless steel joints produced by ultrasonic welding - Ao, S. S. (2022)
(No. U1933129) (No. 18JCQNJC04100, No. 19JCZDJC39000 No. 19YFFCYS00090 UID/00667/2020